Comparison of muscle activity distribution in the biceps brachii using monopolar and bipolar multichannel surface electromyography - Kakeru Ito; Akio Kikuchi; Toshiaki Sato (PLoS ONE, 2025)
The detailed distribution of muscle activity within the biceps brachii (BB) muscle during isometric contraction as contraction intensity increases is not yet fully understood using multichannel surface electromyography (EMG). This study aimed to elucidate the distribution of muscle activity within the BB muscle during isometric contractions using monopolar and bipolar recording methods with multichannel surface EMG. The participants were 23 healthy young adults who performed a gradually increasing load task involving right elbow flexion for 10 seconds. The results showed that muscle activity was higher in the proximal medial area from the middle region with the monopolar recording method, and higher in the central medial area with the bipolar recording method as contraction intensity increased. These results with the monopolar recording method were consistent with previous reports regarding the increased shortening rate of the BB muscle from the middle to the proximal area and the migration of the innervation zone. Therefore, the monopolar recording method of multichannel surface EMG is considered more suitable for clarifying the detailed distribution of muscle activity within the same muscle.